P3.283 Trends and Associations of Neisseria Gonorrhoeae Infection in Men and Women with Genital Discharge Syndromes in Johannesburg, South Africa. (13th July 2013) - Lewis, D A; Ricketts, C; Kekana, V; Vezi, A; Basson, I; Magooa, P; Bhojraj-Sewpershad, N; Gita, G de; Radebe, F; Maseko, V
Abstract : Background: Annual STI aetiological surveys undertaken at a primary healthcare facility in Johannesburg, South Africa, each year have determined the prevalence of gonorrhoea amongst men with male urethral discharge syndrome (MUDS) and women with vaginal discharge syndrome (VDS). We investigated associations between Neisseria gonorrhoeae infection and the demographic, clinical, microbiological and behavioural characteristics of these patients. Methods: During six annual surveys (2007–2012), 1, 218 MUDS and 1, 232 VDS cases were consecutively recruited. Aetiology was determined using nucleic acid amplification assays ( N. gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma genitalium ), microscopy of vaginal smears (bacterial vaginosis, Candida ) and serology (syphilis, HSV-2, HIV). Chi-squared tests and logistic regression analyses were used to identify predictors of N. gonorrhoeae infection. Results: There were no significant trends in the prevalence of gonorrhoea among MUDS and VDS patients. Overall, 908 (74.6%) men and 156 (12.7%) women were N. gonorrhoeae positive, with the highest prevalence observed in men aged 30–34 years (79.1%) and women aged 18–19 years (19.2%). N. gonorrhoeae was detected more often in MUDS patients co-infected with HIV (aOR 2.25, 95% CI, 1.59–3.17) but less often among men with co-existent C. trachomatis (aOR 0.36, 95% CI 0.26–0.49), T. vaginalis (aOR 0.29, 95% CI 0.17–0.50) and M. genitalium infection (aOR 0.15. 95% CI 0.10 – 0.22). In contrast, the presence of N. gonorrhoeae infection in women with VDS was higher in younger women (aOR 0.72, 95% CI 0.63–0.83) and women co-infected with C. trachomatis (aOR 2.23, 95% CI 1.50–3.31). Conclusion: We have demonstrated an important association between gonococcal urethral discharge and HIV co-infection in men, which emphasises the importance of early diagnosis, treatment and prevention of gonorrhoea as a strategy to reduce HIV transmission to serodiscordant partners. Our data also emphasise the fact that VDS patients with gonorrhoea are also at high risk of having co-existent chlamydial infection.